Comparative Evaluation of Antimicrobial Activity of QMiX, 2.5% Sodium Hypochlorite, 2% Chlorhexidine, Guava Leaf Extract and Aloevera Extract Against Enterococcus faecalis and Candida albicans – An in-vitro Study - Jerin Jose; Shoba Krishnamma; Faizal Peedikayil; Shibu Aman; Nithya Tomy; Jithin Pulickal Mariodan (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Debridement and disinfection of the root canal system is a critical step in endodontic treatment. Most of the irrigants presently used in the endodontic treatment can have an impact on the microbes surviving in the biofilm but none of them are able to do all of the required tasks. Researches are going on its full swing in order to produce an endodontic irrigant having ideal properties. Aim: To compare the antimicrobial efficacy of different irrigants like QMiX, guava leaf extract, aloevera extract, 2.5% sodium hypochlorite and 2% chlorhexidine gluconate against Enterococcus faecalis and Candida albicans. Materials and Methods: The antimicrobial activity was determined using agar diffusion test. The solutions were divided into five groups: Group I- QMiX, Group II- Guava leaf extract and Group III-Aloevera extract, Group IV–2.5% Sodium hypochlorite and Group V-2% Chlorhexidine. The zones of inhibition of growth were recorded. Results: Statistical analysis was performed using one way ANOVA with post-hoc Tukey’s HSD. Values obtained were statistically analyzed (p<0.05). QMiX showed maximum inhibitory effect against Enterococcus faecalis and Candida albicans followed by, 2% chlorhexidine, 2.5% sodium hypochlorite, guava leaf extract and aloevera extract. Results obtained were statistically significant. Conclusion: Guava leaf extract showed significant inhibitory effects against Enterococcus faecalis and Candida albicans. QMiX demonstrated the best results among the tested solutions and can be considered as a potential alternative to existing root canal irrigants.